2023
DOI: 10.1186/s40360-023-00671-0
|View full text |Cite
|
Sign up to set email alerts
|

β-sitosterol attenuates high- fat diet-induced hepatic steatosis in rats by modulating lipid metabolism, inflammation and ER stress pathway

Abstract: Nonalcoholic fatty liver disease (NAFLD) is the most prevalent chronic hepatic disorder. The naturally occurring phytosterol; β-sitosterol has antiobesogenic and anti-diabetic properties. The purpose of this study was to explore the role of β-sitosterol in preventing hepatic steatosis induced by a high-fat diet (HFD) in rats. In the current study, to induce NAFLD in the female Wister rats, an HFD was administered to them for 8 weeks. The pathogenic severity of steatosis in rats receiving an HFD diet was dramat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Increased concentrations of chemokines and pro-inflammatory cytokines (IL-10, IL-6, TNF-α), are secreted by synovial tissue. 56 Our findings are in agreement with Abo-Zaid et al who found that serum concentrations of transaminases (ALT and AST), were all diminished by Bs. 57 It was also noticed that TLRs was increased and significantly expressed in synovial fibroblasts even in the early phases of RA, 54 the finding which is in support to our finding.…”
Section: Discussionsupporting
confidence: 93%
“…Increased concentrations of chemokines and pro-inflammatory cytokines (IL-10, IL-6, TNF-α), are secreted by synovial tissue. 56 Our findings are in agreement with Abo-Zaid et al who found that serum concentrations of transaminases (ALT and AST), were all diminished by Bs. 57 It was also noticed that TLRs was increased and significantly expressed in synovial fibroblasts even in the early phases of RA, 54 the finding which is in support to our finding.…”
Section: Discussionsupporting
confidence: 93%
“…IL-1β has been suggested to play an important role in hepatic steatosis, inflammation, and fibrosis. 17 NHR evaluates the body’s inflammatory response and plays an important role in lipid metabolism. NHR may directly influence the body’s inflammatory response and thereby mediate NAFLD development.…”
Section: Discussionmentioning
confidence: 99%
“…However, in both the 2-and 10-sprayed samples, the peaks of vitamins B and E, chalcone, cis-9-hexadecenal, and naphthalene-4a disappeared. Gamma-sitosterol was identified only in the 2-sprayed sample and has anti-diabetic properties and hepato-protectant [22][23][24]. The peak at 3336cm -1 corresponds to N-H-groups typical of capsaicin.…”
Section: Gc-ms Figure 4(a)mentioning
confidence: 99%